Particle Counting Methods Based on Microfluidic Devices - Dang, Zenglin; Jiang, Yuning; Su, Xin; Wang, Zhihao; Wang, Yucheng; Sun, Zhe; Zhao, Zheng; Zhang, Chi; Hong, Yuming; Liu, Zhijian (Micromachines (Basel), 2023)
Particle counting serves as a pivotal constituent in diverse analytical domains, encompassing a broad spectrum of entities, ranging from blood cells and bacteria to viruses, droplets, bubbles, wear debris, and magnetic beads. Recent epochs have witnessed remarkable progressions in microfluidic chip technology, culminating in the proliferation and maturation of microfluidic chip-based particle counting methodologies. This paper undertakes a taxonomical elucidation of microfluidic chip-based particle counters based on the physical parameters they detect. These particle counters are classified into three categories: optical-based counters, electrical-based particle counters, and other counters. Within each category, subcategories are established to consider structural differences. Each type of counter is described not only in terms of its working principle but also the methods employed to enhance sensitivity and throughput. Additionally, an analysis of future trends related to each counter type is provided.